PENGARUH PENDAPATAN DAN KARAKTER TERHADAP KREDIT NASABAH PEMBIAYAAN PADA BADAN KERJASAMA NAGARI (BKN) PARIK - RISKA NURVADILA (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2023)
This research is motivated by the role of the MSME business sector that can affect national welfare. In this case, the researcher relates the problem of customer income and customer character with financing customer credit at the Parik Nagari Cooperation Agency (BKN). This study aims to partially examine and how the income and character of the financing customer credit at the Nagari Cooperation Agency (BKN) parik. In this study, the sample is customers in the Nagari Cooperation Agency. This study uses quantitative research, the number of samples taken, the researcher uses the opinion of Roscoe, that if the research will perform multivariate analysis (correlation or multiple regression for example), the number of members who sample is at least 10 times the number of variables studied. In this study, researchers used multiple regression analysis with 3 variables. So, the number of samples that the researchers took was 30 sample members at each financial institution. The type of data used in this study is primary data. Data collection techniques using questionnaires. The data analysis technique used in this research is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, hypothesis test. The results of this study concluded that income and character have an influence on customer credit financing. This is evidenced by the results of the F test showing that the value of fcount > ftable, where the value of fcount is 14,874 which is greater than ftable of 3.35, it can be interpreted that together there is an influence between income and character on financing customer credit at the Nagari Cooperation Agency (BKN). Parik. Based on the results of the partial test calculation (t test) the significant value of the income variable is 0.921, because the value of sig. 0.921 > 0.05 it can be concluded that Ho is accepted and Ha is rejected. This means that there is no effect of income on the credit of financing customers. The significant value of the character variable is 0.000, because the sig. 0.000 < 0.05 then it can be concluded that Ha is accepted and Ho is rejected. This means that there is an influence of character on the credit of financing customers. Based on the results of the calculation of the coefficient of determination (R2), it is shown that the value of R square the amount of variation in the dependent variable is influenced by the independent variable is 52.4%, while the remaining 47.6% is influenced by other variables.